Point of care and oral fluid hepatitis B testing in remote Indigenous communities of northern Australia. Issue 4 (22nd December 2019) - Sullivan, Richard P.; Davies, Jane; Binks, Paula; Dhurrkay, Roslyn Gundjirryiir; Gurruwiwi, George Garambaka; Bukulatjpi, Sarah Mariyalawuy; McKinnon, Melita; Hosking, Kelly; Littlejohn, Margaret; Jackson, Kathy; Locarnini, Stephen; Davis, Joshua S.; et al.
Abstract: Many Indigenous Australians in northern Australia living with chronic hepatitis B are unaware of their diagnosis due to low screening rates. A venous blood point of care test (POCT) or oral fluid laboratory test could improve testing uptake in this region. The purpose of this study was to assess the field performance of venous blood POCT and laboratory performance of an oral fluid hepatitis B surface antigen (HBsAg) test in Indigenous individuals living in remote northern Australian communities. The study was conducted with four very remote communities in the tropical north of Australia's Northern Territory. Community research workers collected venous blood and oral fluid samples. We performed the venous blood POCT for HBsAg in the field. We assessed the venous blood and oral fluid specimens for the presence of HBsAg using standard laboratory assays. We calculated the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of the POCT and oral fluid test, using serum laboratory detection of HBsAg as the gold standard. From 215 enrolled participants, 155 POCT and 197 oral fluid tests had corresponding serum HBsAg results. The POCT had a sensitivity of 91.7% and specificity of 100%. Based on a population prevalence of 6%, the PPV was 100% and NPV was 99.5%. The oral fluid test had a sensitivity of 56.8%, specificity of 98.1%, PPV of 97.3% and NPV of 65.9%. The venous blood POCT has excellent test characteristics and could be used to identify individuals with chronic HBV infection in high prevalence communities with limited access to health care. Oral fluid performance was suboptimal.